Sistem Pembelajaran PAI Berwawasan Multikultural - Sunarto, Sunarto (Al-Tadzkiyyah: Jurnal Pendidikan Islam, 2016)
Starting from the question of why and what the background of the need for the holding of "Multicultural Education" and included in the curriculum PAI? For, if the goal is to live in peace with the followers of the other since the beginning of Islam already exemplifies it. In the book PINM-PAI SMA / SMK mentioned examples of Medina Charter that guarantees social life for the followers of other religions. Logically, it should be explained that the curriculum PAI has been no less insightful or multicultural so that the curriculum needs to be changed.               If there is, on which part? We do not close you to the term or new concepts from outside Islam as multiculturalism but the term was clarified its meaning. If not in accordance with the view of nature (worldview) of Islam, then it should be given a new meaning, as do the preachers of Islam in the archipelago the Islamization of the term "heaven, hell, reward, sin, devotion," and so on. Do not get the impression that "Multicultural Education" we enter into the curriculum PAI because of external pressure or take advantage of opportunities that promise financial availability.               Already we both understand, long before the term multicultural, conceptually as well as in the historical reality, Islam is a religion that proved successful in realizing a multicultural society in Medina, Baghdad, Palestine, Andalusia and so forth. In Medina, the Prophet Muhammad pioneered a country with a written Constitution, the world first. In Palestine, Caliph Umar bin Khattab was the first leader in the world are on religious freedom in the Islamic perspective on the city of Jerusalem, in 636 AD